Sterically Hindered Amination of Aryl Chlorides Catalyzed by a New Carbazolyl-Derived P,N-Ligand-Composed Palladium Complex - Lai, Wing In; Leung, Man Pan; Choy, Pui Ying; Kwong, Fuk Yee (Synthesis, 2019)
A family of 2-(9H-carbazol-9-yl)phenyl-based phosphine ligands were synthesized and their efficacy in promoting the steric hindered Buchwald–Hartwig amination was evaluated. In the presence of Pd(OAc)2 (0.03–1.0 mol%) associated with the newly developed a carbazolyl-derived phosphine ligand, the synthesis of tetra-ortho-substituted diarylamines proceeded smoothly with excellent product yields (up to 99%). A remarkable result was obtained even for the coupling of highly sterically congested 2,6-diisopropylaniline and hindered 2-chloro-1,3,5-triisopropylbenzene (96% isolated yield). A possible decomposition pathway for the anthracenyl C–N coupling product is also reported.
Keywords: palladium; amination; aryl chlorides; phosphine; sterically congested